2014
DOI: 10.1098/rsbl.2014.0592
|View full text |Cite
|
Sign up to set email alerts
|

Marching into battle: synchronized walking diminishes the conceptualized formidability of an antagonist in men

Abstract: Paralleling behaviours in other species, synchronized movement is central to institutionalized collective human activities thought to enhance cooperation, and experiments demonstrate that synchrony has this effect. The influence of synchrony on cooperation may derive from an evolutionary history wherein such actions served to signal coalitional strength to both participants and observers-including adversaries. If so, then synchronous movement should diminish individuals' estimations of a foe's formidability. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(50 citation statements)
references
References 31 publications
3
45
2
Order By: Relevance
“…Similarity of personality among group members may be beneficial in species with group-level cooperation and coordination. Similarity in behavioural tendencies among group members increases coordination and prosociality454647, because similar affective states result in a cognitively inexpensive way of facilitating behavioural synchrony, contingency and reciprocity4849. Closely cooperating individuals have similar personalities in humans475051 and chimpanzees52.…”
Section: Discussionmentioning
confidence: 99%
“…Similarity of personality among group members may be beneficial in species with group-level cooperation and coordination. Similarity in behavioural tendencies among group members increases coordination and prosociality454647, because similar affective states result in a cognitively inexpensive way of facilitating behavioural synchrony, contingency and reciprocity4849. Closely cooperating individuals have similar personalities in humans475051 and chimpanzees52.…”
Section: Discussionmentioning
confidence: 99%
“…Collective action against other groups is different because the required level of coordination and effort is always relative to the opposing group. Whether collective coalitional action is sufficient is a moving target, and group conflict is essentially an arms race between the groups about being the best-coordinated and most-investing group (Bowles, 2009;Fessler & Holbrook, 2014). In other words: All else equal, coalitional conflict places greater demands on the investments and coordination of group members than many other types of collective action.…”
Section: Trade-offs In Followership Decisionsmentioning
confidence: 99%
“…However, this is not the only starting point for such theorizing. Coming at the problem of cooperation from the perspective of prior work on postural mirroring (LaFrance, 1985), LaFrance (1990) offered a brief theoretical sketch that, while lacking ultimate explanations or phylogenetic accounts, nevertheless directly parallels Hagen et al's perspective on the informational value of synchrony in communicating cohesiveness to both in-group and out-group individuals.Although Hagen and Bryant's signaling paper has been highly cited in work exploring the psychology of synchrony, consonant with McNeill's initial focus, to date, much of this literature has focused not on outwardly signaling coalitional quality in the service of intimidating rivals and attracting allies, but rather on the subjective and behavioral consequences of participation in synchrony, particularly as they pertain to issues of conformity, cohesion, bonding, solidarity, prosociality, and cooperation (see, for example, Wiltermuth & Heath, 2009;Hove & Risen, 2009;Cohen et al, 2010;Kirschner & Tomasello, 2010;Valdesolo et al, 2010;Kokal et al, 2011;Valdesolo & DeSteno, 2011;Wiltermuth, 2012b;Wiltermuth, 2012a;Fischer et al, 2013;Launay et al, 2013;Reddish et al, 2013a;Reddish et al, 2013b; Kirschner & Ilari, 4 2014;Cirelli et al, 2014a;Cirelli et al, 2014b;Fessler & Holbrook, 2014;Lumsden et al, 2014;Sullivan et al, 2014;Dong et al, 2015;Rabinowitch & Knafo-Noam, 2015;Sullivan et al, 2015;Tarr et al, 2015;Zimmermann & Richardson, 2015; Tarr et al, in press; see also Weinstein et al, 2016). In contrast, the question of the interpretation of signals by non-participants has received less attention in this body of work (see Dong et al, 2015, as well as Lumsden et al, 2012, for exceptions).…”
mentioning
confidence: 99%
“…Wiltermuth demonstrated that experimentally induced synchrony increases compliance with instructions to aggress against an outgroup (2012b) or destroy insects (2012a), and we have previously shown that walking in synch with another man decreases men's estimations of the physical formidability of a hypothetical antagonist (Fessler & Holbrook 2014), a measure that, as we discuss below, has been demonstrated to summarize the threat that a hostile other is seen as posing. However, while addressing aggression and conflict, all three of these findings pertain exclusively to the effects of synchrony on those participating in it, and thus do not speak to a key feature of the signaling model, namely the affordances for communicating features of the synchronized group to outsiders.…”
mentioning
confidence: 99%
See 1 more Smart Citation